A renewed focus on the REMS system: from Investigation Order no. 131 of 2021 to Judgment no. 22 of 2022 of the Constitutional Court (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The article starts from the examination of two recent rulings of the Constitutional Court concerning the system of Residences for the execution of security measures (order n. 131/2021 and sentence n. 22/2022). At the outcome of the preliminary investigation and of the unconstitutionality, detected but not declared, it emerges that the evolution path of the system of detention security measures, which has gone from hospitalization in judicial psychiatric hospitals to placement in exclusively healthcare management structures, it is still in progress. In fact, interventions are necessary to overcome the main criticalities of this system (including waiting lists), which, in order to be effective, require a serious political and financial commitment.
Keywords: Security measures; investigation order of the Constitutional Court; unconstitutionality detected but not declared; waiting lists